Moderate hypoxia induces metabolic divergence in circulating monocytes and tissue resident macrophages from Berkeley sickle cell anemia mice - Lisk, Christina; Cendali, Francesca; Pak, David I.; Swindle, Delaney; Hassell, Kathryn; Nuss, Rachelle; George, Gemlyn; Davizon-Castillo, Pavel; Buehler, Paul W.; D’Alessandro, Angelo; Irwin, David C. (Frontiers in Medicine, 2023)
Human and murine sickle cell disease (SCD) pulmonary hypertension (PH) is defined by hemolysis, persistent nitric oxide depletion, inflammation and thrombosis. Further, hemoglobin (Hb), heme, and iron accumulation are consistently observed in pulmonary adventitial macrophages at autopsy and in murine models of SCD which show distribution of ferric and ferrous Hb as well as HO-1 and ferritin heavy chain. In addition, the anatomic localization of these macrophages is consistent with areas of significant vascular remodeling and their potential contributions toward progressive disease may diverge from some of the mechanism of idiopathic and other forms of pulmonary arterial hypertension (PAH). However, concomitant and overlapping processes of pulmonary vascular disease progression likely exist. These processes may also extend to the vasculature of other organs, such as the cerebral vasculature that are consistently impaired in advanced SCD. To date limited information is available on the metabolism of macrophages or monocytes isolated from pulmonary, spleen, and peripheral blood in humans or murine models of SCD. Here we hypothesize that metabolism of macrophages and monocytes isolated from this triad of tissue differs in aged moderately hypoxic Berk mice compared to aged normoxic counterparts and wild type mice under matched conditions. This study represents an initial set of data that for the first time describes the metabolism in monocytes and macrophages in peripheral blood mononuclear cells, lung and spleen.